الإطار النظري للحكومة الالكترونية في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research defines e-government as a new method of providing services to citizens in order to raise the efficiency of government performance and reduce the routine procedures suffered by citizens and provide information and data in an easy way to benefit from the enormous digital revolution, The application of the e-government system requires the availability of many capabilities in order to provide excellent service to the citizen and to achieve an appropriate level of performance for public administration organizations at the same time. This study seeks to clarify that e-government should be a means of building a strong economy that contributes to solving problems Economic and social services that contribute to the building of a strong society, a means of interaction with high performance and lower cost, and also a means of performing all the delays and slow delivery of services. يقوم هذا البحث بالتعريف بالحكومة الالكترونية التي تمثل أسلوبا جديداً لتقديم الخدمات للمواطن بهدف رفع كفاءة الأداء الحكومي وخفض الإجراءات الروتينية التي يعانى منها المواطنون وتوفير المعلومات والبيانات بطريقة سهلة للاستفادة من الثورة الرقمية الهائلة, وما يتطلبه تطبيق نظام الحكومة الالكترونية من توافر العديد من الإمكانات بهدف تقديم خدمة متميزة للمواطن، وتحقيق مستوى أداء مناسب لمنظمات الإدارة العامة (الحكومية) في نفس الوقت إن هذه الدراسة تسعى إلى توضيح إنّ الحكومة الإلكترونيّة يتعيّن أنْ تكون وسيلة بناء اقتصاد قويّ تسهم في حلّ المشكلات الاقتصاديّة، وتكون وسيلة خدمة اجتماعيّة تسهم في بناء مجتمع قويّ، ووسيلة تفاعل بأداء عالٍ وتكلفة أقلّ، وهي أيضاً وسيلة أداء باجتياز كلّ مظاهر التأخير والبطء في تقديم الخدمات.